2003
DOI: 10.1176/appi.ajp.160.5.996
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled Study of the Omega-3 Fatty Acid Docosahexaenoic Acid in the Treatment of Major Depression

Abstract: This trial failed to show a significant effect of DHA monotherapy in subjects with major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
242
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(250 citation statements)
references
References 8 publications
6
242
0
2
Order By: Relevance
“…It was recently reported that the administration of pure EPA was beneficial for treatment of major depression (Nemets et al, 2002), but DHA was not effective (Marangell et al, 2003). Peet and Horrobin (2002) also reported the beneficial effects of pure EPA on major depression.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that the administration of pure EPA was beneficial for treatment of major depression (Nemets et al, 2002), but DHA was not effective (Marangell et al, 2003). Peet and Horrobin (2002) also reported the beneficial effects of pure EPA on major depression.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies suggest that a low dietary n-3 PUFA intake can increase human locomotor activity, aggression, and depression, as well as the prevalence of bipolar disorder and other psychiatric and neurodegenerative diseases in which these symptoms may be prominent (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). However, to date, most of these epidemiological correlations have not been tested or confirmed in controlled clinical trials (36,37).…”
mentioning
confidence: 99%
“…A second randomized control trial involved 36 depressed patients who were randomly assigned to receive 2 g d -1 DHA or placebo for 6 weeks. In this work, response rates were 27.8% in the DHA group and 23.5% in the placebo group, numbers that did not achieve statistical significance [63]. Some studies have also evaluated the use of a fatty acid supplement in addition to a conventional antidepressant regimen.…”
Section: Fish Oils and Fatty Acidsmentioning
confidence: 74%